The Grass Was Greener-Climate Change, One Health, and the High Hopes to Mitigate COVID-19, Avian Influenza, and other Zoonotic Emerging Diseases (2021)
Over the last decades, global warming has significantly affected the world’s climate, negatively impacting numerous ecosystems (Cardenas et al., 2006; Beyer et al., 2021; Dupraz and Burnand, 2021). The accumulating influences of climate change, including the rise of the earth’s surface temperature and sea level as well as melting glaciers among many other direct and indirect effects (Calel et al., 2020; Harvey et al., 2020), are reshaping, not only the ecological landscape of many world regions, but also setting the stage for emerging diseases sceneries. Floods, droughts, hurricanes (Zambrano et al., 2021), heat waves and surging fires across all continents (Bonilla-Aldana et al., 2019) are all part of the human-driven fingerprint that has led to climate change (Figure 1). These effects have also resulted in a massive reduction of vegetation across many regions around the globe. As the legendary British rock 'n' roll band Pink Floyd once sang in their most celebrated song “High Hopes”, “…the grass was greener…” (Pink Floyd, dixit), framed in an environmental context these lyrics should call for a reflection on how climate change is leaving its mark on earth’s landscape